Caso de estudio: la auditoria administrativa aplicada en una empresa - Durán Salazar, Galo Mauricio (2018)
The objective of the research is to show the methodology and results of an administrative audit done in a company that in this case was called "case study", it was tried to determine the level of compliance that the company has with the control organisms. The importance of an audit of this type involves reviewing the administrative and accounting processes in order to detect weaknesses that allow corrections and favor the continuity of the business. The investigation was of documentary type, used as instruments interviews to key personnel of the company, review of documents facilitated by the company, and the methodology COSO. The results of the research indicated that the company's case study had a confidence level of 66% which is moderate, generating a level of risk of 34%. The shortcomings detected were that there are no specific function manuals for employees and that the activities carried out by the workers are combined, which is a risk, given the lack of responsibilities on the part of the staff. Another situation was that management and the financial area have little communication and the area responsible for the company ends up being the financial area. These two situations are recommended should be resolved for the improvement of the business